Divergent social communication between autistic and non-autistic individuals revisited: unraveled via an Integrated Model of Pragmatic Competence - Xu, Chang; Mao, Tiaoyuan; Du, Shengbin (Frontiers in Psychology, 2023)
Some current studies call for adopting the theory of the Double Empathy Problem (DEP) to reappraise autistic individuals' problematic social communications with non-autistic individuals from the perspectives of both sides, rather than exclusively focusing on the social cognition of individuals with autism. However, there is no specific proposal that explicates how such reframed social communications proceed. Herein, we adopt two subcomponents of the Integrated Model of Pragmatic Competence (IMPC) to clarify the main factors leading to the divergent social interactions between the two groups. Internal Pragmatic Competence (IPC), revealing how they both independently think about internal linguistic and communicative issues, echoes DEP's reference to different mindsets and elucidates why the uncooperative social communications happen. Pragmatic Competence for External Communication (PCEC) explains how the impaired communications among organism-internal submodules and/or their unsuccessful interactions with outside contexts impede the external sociopragmatic communications between the two sides. Put together, the operation of the two components helps interpret the cognitive pragmatic mechanism underlying the social communications and suggests a potential holistic perspective to improve such communications in terms of both sides.